The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1213/ane.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Acute Normovolemic Hemodilution for Minimizing Allogeneic Blood Transfusion

Abstract: Although these results suggest that PANH is effective in reducing allogeneic blood transfusion, we identified significant heterogeneity and publication bias, which raises concerns about the true efficacy of PANH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 66 publications
(69 reference statements)
0
42
0
7
Order By: Relevance
“…Acute normovolemic hemodilution (ANH), a technique performed immediately prior to a procedure at high risk for blood loss, has been shown to reduce the need for allogenic transfusion [9]. During ANH, whole blood is removed from the patient and replaced with a crystalloid/colloid mixture to maintain euvolemia.…”
Section: Introductionmentioning
confidence: 99%
“…Acute normovolemic hemodilution (ANH), a technique performed immediately prior to a procedure at high risk for blood loss, has been shown to reduce the need for allogenic transfusion [9]. During ANH, whole blood is removed from the patient and replaced with a crystalloid/colloid mixture to maintain euvolemia.…”
Section: Introductionmentioning
confidence: 99%
“…Our results further supported previous findings that the use of ANH could reduce intraoperative RBC transfusions in patients undergoing cardiac surgery [ 6 , 7 , 21 ], even though blood loss was similar between the ANH and non-ANH groups in our study. Some meta-analysis also supported that ANH is effective in minimizing blood transfusion in patients undergoing cardiac surgery [ 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also an increasing concern about the improved outcomes associated with ANH [ 7 , 13 , 14 ]; the safety of ANH still remains uncertain [ 15 ]. We performed this study to assess the relationship between mild volume ANH, perioperative transfusions, and outcomes in Chinese patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that large volume hemodilution was associated with adverse complications. [ 22 , 23 ] Finally, although the strict exclusion criteria was assumed to minimize biases, the potential bias factors, such as population characteristics, may not be completely eliminated in our study.…”
Section: Discussionmentioning
confidence: 99%